Angiotensin-converting enzyme 2 (ACE2) receptor and SARS-CoV-2: Potential therapeutic targeting - Sharifkashani, Sourena; Bafrani, Melika Arab; Khaboushan, Alireza Soltani; Pirzadeh, Marzieh; Kheirandish, Ali; Yavarpour_Bali, Hanie; Hessami, Amirhossein; Saghazadeh, Amene; Rezaei, Nima (European journal of pharmacology, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a beta coronavirus that uses the human angiotensin-converting enzyme 2 (ACE2) receptor as a point of entry. The present review discusses the origin and structure of the virus and its mechanism of cell entry followed by the therapeutic potentials of strategies directed towards SARS-CoV2-ACE2 binding, the renin-angiotensin system, and the kinin-kallikrein system. SARS-CoV2-ACE2 binding-directed approaches mainly consist of targeting receptor binding domain, ACE2 blockers, soluble ACE2, and host protease inhibitors. In conclusion, blocking or manipulating the SARS-CoV2-ACE2 binding interface perhaps offers the best tactic against the virus that should be treated as a fundamental subject of future research.